Principal supervision in enhancing middle school teachers' professionalism - Tarso Tarso; Priadi Surya; Rif’an Efendi; Rohmanur Mala (Curricula: Journal of Curriculum Development, 2025)
Supervision has a strategic role in improving the quality of teaching and teacher professionalism in the school environment. This study describes the principal's supervision strategy in improving teacher professionalism at SMP Muhammadiyah 2 Samigaluh. The study used a qualitative method with data collection techniques in the form of interviews, observations, and documentation. The study results indicate that academic supervision is designed through annual and semester programs, including learning administration, teaching and learning activities, and evaluation. The implementation of supervision is carried out individually and in groups with a collaborative approach involving the principal and the supervision team. Evaluation supervision is carried out every semester to identify strengths and weaknesses and design teacher competency improvement programs. Supervision also encourages professional development through training, workshops, and mentoring. Supporting factors for supervision include positive teacher attitudes, harmonious relationships, and periodic training. Obstacles include limited time, teacher mental readiness, and limited facilities and budget. Planned, evaluative, and adaptive supervision has created an effective and professional learning environment.   Abstrak Supervisi mempunyai peran yang strategis dalam meningkatkan mutu pengajaran dan profesionalisme guru dalam lingkungan sekolah. Penelitian ini bertujuan mendeskripsikan strategi supervisi kepala sekolah dalam meningkatkan profesionalisme guru di SMP Muhammadiyah 2 Samigaluh. Penelitian menggunakan metode kualitatif dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa supervisi akademik dirancang melalui program tahunan dan semesteran yang mencakup administrasi pembelajaran, kegiatan belajar mengajar, dan evaluasi. Pelaksanaan supervisi dilakukan secara individual dan kelompok dengan pendekatan kolaboratif yang melibatkan kepala sekolah dan tim supervisi. Evaluasi supervisi dilakukan setiap semester untuk mengidentifikasi kekuatan dan kelemahan serta merancang program peningkatan kompetensi guru. Supervisi juga mendorong pengembangan profesional melalui pelatihan, lokakarya, dan pendampingan. Faktor pendukung supervisi meliputi sikap positif guru, hubungan harmonis, dan pelatihan berkala. Kendala yang dihadapi antara lain keterbatasan waktu, kesiapan mental guru, serta fasilitas dan anggaran yang terbatas. Supervisi yang terencana, evaluatif, dan adaptif terbukti berkontribusi dalam menciptakan lingkungan belajar yang efektif dan profesional. Kata Kunci: kepala sekolah; profesionalisme guru; sekolah menengah pertama; supervisi akademik